Social Support and Arabic Language Fluency: An Analysis of Student Interaction Quality - Aqil , Abdurrahman Ahmad; Husein, Achmad Fairuz; Arifin, Ahmad; Zidan Muhtadin Husni (Program Studi Pendidikan Bahasa Arab, 2025)
This study investigates the impact of social support on enhancing Arabic language fluency, with a specific focus on speaking skills among students at Dalwa. Employing a qualitative approach grounded in Social Support Theory, the research involved in-depth interviews with 30 students and 5 lecturers, alongside participatory classroom observations. Findings reveal that emotional support, including peer encouragement and motivational feedback, significantly bolsters students’ confidence, while practical support, such as lecturer feedback and collaborative learning, directly improves speaking competence. Despite the positive influence of social support, challenges such as language anxiety and fear of public mistakes persist, particularly during formal speaking activities. The study highlights the importance of fostering supportive educational environments where emotional security and constructive feedback are prioritized. Furthermore, the results align with broader theoretical frameworks, including Self-Determination Theory and Ecological Systems Theory, emphasizing the interconnected role of emotional, academic, and environmental factors in second language acquisition. This research contributes contextual insights into Arabic language learning within Islamic higher education institutions, offering practical recommendations for integrating social support mechanisms into pedagogical strategies to enhance students' speaking proficiency.